Dorsal Dupuytren's disease: a systematic review of published cases and treatment options. (November 2019) - Carloni, Raphael; Gandolfi, Silvia; Elbaz, Benedicte; Bonmarchand, Albane; Beccari, Roberto; Auquit-Auckbur, Isabelle
Dorsal lesions in Dupuytren's disease are rare and data concerning their epidemiology and management are sparse. We conducted a systematic review to summarize reported cases of dorsal Dupuytren's disease. Pubmed, Cochrane, and Embase databases were searched from 1893 to 2018, and 17 articles were selected (525 patients). The male to female ratio was 3.8:1. The dorsal disease was bilateral in 225 patients (50%). The index was the most commonly affected finger (48 patients). The proximal interphalangeal joint was the most commonly affected (484 cases). The most frequently reported lesions were knuckle pads (503 patients), dorsal nodules between interphalangeal joints (14 patients), boutonnière deformities (12 patients), and swan-neck deformities (2 patients). Nearly half of the included patients were treated surgically. Postoperative functional result depended on the treated lesion. Most of the included studies had a low level of evidence. Higher-quality studies are necessary to confirm our findings.